2021
DOI: 10.1029/2021gl092466
|View full text |Cite
|
Sign up to set email alerts
|

Magnetospheric Multiscale Observations of the Source Region of Energetic Electron Microinjections Along the Duskside, High‐Latitude Magnetopause Boundary Layer

Abstract: The present paper demonstrates the first observations by the Magnetospheric Multiscale (MMS) mission of the counter‐streaming energetic electrons and trapped energetic protons, localized in the magnetic field depressions between the mirror mode peaks, in the Earth's dusk sector high‐latitude magnetosphere. This region is characterized by high plasma beta, strong ion temperature anisotropy, and intermediate plasma density between magnetospheric and magnetosheath plasma. We show that these plasma conditions are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 53 publications
2
16
0
Order By: Relevance
“…B z and the plasma pressure were anti‐phase with β . β had a large value (∼3) when observing intense discrete arcs in keogram, and the drift mirror instability parameter was much larger than 1 after 15:50 UT (Nykyri et al., 2021). Similar to the previous event, the high β value, high drift mirror instability parameter and anti‐correlation between the thermal and magnetic pressures suggest slow or drift mirror mode waves.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…B z and the plasma pressure were anti‐phase with β . β had a large value (∼3) when observing intense discrete arcs in keogram, and the drift mirror instability parameter was much larger than 1 after 15:50 UT (Nykyri et al., 2021). Similar to the previous event, the high β value, high drift mirror instability parameter and anti‐correlation between the thermal and magnetic pressures suggest slow or drift mirror mode waves.…”
Section: Resultsmentioning
confidence: 99%
“…B x and B y were much smaller than B z . β (P i /P b , Figures 1Af and 1Bf) was above ∼1, and the drift mirror instability parameter (β ⊥ (P ⊥ /P ‖ − 1), Figures 1Ah and 1Bh) (Nykyri et al, 2021) was much larger than 1, indicating that the satellites were in the central plasma sheet and the drift mirror mode waves were unstable. THEMIS D had slightly smaller β (∼1.2 after 13:38 UT) compared with THEMIS E (∼1.5 after 13:38 UT), suggesting that THEMIS E was slightly closer to the neutral sheet than THEMIS D. The vertical lines mark individual peaks of β oscillations after 13:38 UT.…”
Section: Event 1 On 7 November 2007mentioning
confidence: 98%
“…Kavosi et al (2018) suggested that the bi-directional electrons are associated with KHW and FTEs at the dusk magnetopause. Nykyri et al (2021) considered that the source regions of these electrons are the diamagnetic cavities caused by magnetic reconnection in the duskside magnetospheric boundary. Nevertheless, our observations show that electrons of all pitch angles simultaneously get acceleration/deceleration in microinjections.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Recently, Nykyri et al. (2021) observed high fluxes of non‐dispersive counter‐streaming energetic electrons in the high‐latitude duskside magnetopause boundary layer from MMS data. They suggested that this could be a potential source region for the previously reported dispersive microinjection events, and the enhancements of electron fluxes were due to the Fermi mechanism in cavities of the mirror mode wave caused by low‐latitude reconnection for southward and duskward interplanetary magnetic field (IMF).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the ultimate fate of these particles is another important aspect. It is possible that they provide some of the seed population to the radiation belts (Boyd et al., 2016; Nykyri et al., 2021; Tang et al., 2017) or escape to the magnetosheath (Cohen et al., 2017).…”
Section: Introductionmentioning
confidence: 99%